Significance of Private Equity Investments, Especially for SMEs - Blessing or Curse? - Markus Peskes; Fabian Tang Zheng (ZBW – Leibniz Information Centre for Economics, 2024)
Although fallen into disrepute Corporate financing in the form of private equity has developed into a billion-dollar industry. Private equity arose from the need for alternative financing options and has had a long lasting impact on the economy and society. Companies of this sector, which is often described as non-transparent, regularly make headlines because of leveraged buy-outs (LBOs). This multifaceted industry provides various forms of equity capital outside regulated capital markets and should be viewed in a more differentiated manner, especially considering its growing significance for SMEs. The peculiarities of private equity extend beyond just conceptual delineation and its structures, reaching into the methods aimed at achieving excess returns over the public market. This excess return is offset by a range of value enhancement methods and private equity undoubtedly can exert significant influence on companies. Therefore, a holistic view of this industry seems warranted. Accordingly, this research paper examines private equity investments focusing on the mid-market in terms of their sustainable value contributions for investors and companies. It explores whether private equity is more of a blessing or a curse especially for SMEs.
Keywords: G2; G23; G24; 330; SME; LBO; Finance; Private Equity; Leveraged Buy Out; Controlling; M&A